2013
DOI: 10.1073/pnas.1308936110
|View full text |Cite
|
Sign up to set email alerts
|

Ptr-miR397a is a negative regulator of laccase genes affecting lignin content in Populus trichocarpa

Abstract: Laccases, as early as 1959, were proposed to catalyze the oxidative polymerization of monolignols. Genetic evidence in support of this hypothesis has been elusive due to functional redundancy of laccase genes. An Arabidopsis double mutant demonstrated the involvement of laccases in lignin biosynthesis. We previously identified a subset of laccase genes to be targets of a microRNA (miRNA) ptr-miR397a in Populus trichocarpa. To elucidate the roles of ptr-miR397a and its targets, we characterized the laccase gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
339
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 358 publications
(358 citation statements)
references
References 41 publications
10
339
0
4
Order By: Relevance
“…These two sequencerelated Ptr-MYBs share eight common targets, of which five are laccase genes (Ptr-LAC14, Ptr-LAC15, Ptr-LAC40, Ptr-LAC41, and Ptr-LAC49). Using transgenic P. trichocarpa overexpressing a microRNA (miRNA), ptr-miR397a, we recently demonstrated that this miRNA and many TF genes, including Ptr-MYB021, regulate directly 13 laccase (including Ptr-LAC14, Ptr-LAC15, Ptr-LAC40, Ptr-LAC41, and Ptr-LAC49) and four peroxidase (Ptr-PO) genes in a transcriptional regulatory network controlling lignin content during wood formation (Lu et al, 2013). These miRNA transgenic results strongly supported the accuracy of developed top-down algorithm (Figure 4) for predicting the direct TF-DNA relationships.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These two sequencerelated Ptr-MYBs share eight common targets, of which five are laccase genes (Ptr-LAC14, Ptr-LAC15, Ptr-LAC40, Ptr-LAC41, and Ptr-LAC49). Using transgenic P. trichocarpa overexpressing a microRNA (miRNA), ptr-miR397a, we recently demonstrated that this miRNA and many TF genes, including Ptr-MYB021, regulate directly 13 laccase (including Ptr-LAC14, Ptr-LAC15, Ptr-LAC40, Ptr-LAC41, and Ptr-LAC49) and four peroxidase (Ptr-PO) genes in a transcriptional regulatory network controlling lignin content during wood formation (Lu et al, 2013). These miRNA transgenic results strongly supported the accuracy of developed top-down algorithm (Figure 4) for predicting the direct TF-DNA relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Step II (Figure 4), which we developed previously (Lu et al, 2013), uses a partial correlation-based graphical Gaussian model (GGM) (Whittaker, 1990;Edwards, 2000) for a vigorous assessment of direct interactions between Ptr-SND1-B1 and responsive genes to infer Ptr-SND1-B1's direct targets. SDX protoplasts were isolated using the dipping method and transfected with Ptr-SND1-B1 to result in 178 DEGs based on RNA-seq analysis.…”
Section: Gene Ontology Functional Enrichment Analysis Indicates Cellmentioning
confidence: 99%
See 3 more Smart Citations